Hubungan Karakteristik dengan Tingkat Pengetahuan Perawat Tentang Tuberculosis (TB) Paru pada Anak - Fadhilah Rosyid Pradana; Sri Widiyati; Arwani Arwani (Poltekkes Kemenkes Semarang, 2020)
Background: Tuberculosis (TB) in children needs special attention. Enforcement of the diagnosis of childhood TB which is an important component in controlling pulmonary TB itself. Nurses as health workers have a role as providers of nursing care, educators, communicators and extension agents needed in an effort to overcome diseases including pulmonary TB in children. The nurse is also one of the human resources or health workers trained and responsible for implementing pulmonary TB prevention programs. For this reason nurses are required to have competent knowledge.Purpose: To determine the relationship of characteristics with the level of knowledge of nurses about pulmonary TB in children in the Health Center’s area of Semarang City.Methods:.This study used a descriptive survey design with a cross sectional study design. The sampling technique uses purposive sampling. The number of respondents was 44 respondents. The instruments used were questionnaires about demographic data and the level of knowledge about pulmonary TB in children. The data was analised using chi square.Results:.The results of this study using the Chi-square test obtained p value (Age 0.677), (Gender 0.531), (Education Level 0.230), and (Working Period 0.424) which shows p-value 0.05.Conclusion: There is no correlation between the characteristics and level of knowledge of nurses about pulmonary TB in children in Health Center’s area of Semarang.